Milk Yield and Quality to Estimate Genetic Parameters in Buffalo Cows - Sarubbi, Fiorella; Auriemma, Giuseppe; Baculo, Rodolfo; Palomba, Raffaele (Journal of Buffalo Science, 2012)
The objective of this study was to estimate genetic parameters for daily milk yield, fat and protein milk contents and their relationship with "mozzarella" cheese production using the classic instruments of the quantitative genetics. A total of 5130 daily milk yields records, belonging to 6 herds in South Italy were analyzed. The traits studied were: accumulated 270-day milk yield, milk fat and protein percentages, milk yield/day and mozzarella production. Descriptive statistics of the variables studied have been obtained with the procedure MEANS and FREQ, while the variation sources have been investigated using GLM procedure. With the objective to characterize the effects of greater impact on the production of milk (kg/days), fat and protein content (%) and "mozzarella" production (kg/days), has been used analysis of variance (ANOVA). On average, buffalo cow’s milk production during lactation was 9.21±2.79 kg/d with 8.73% of fat and 4.98% of protein. Heritability estimates were low. The genetic correlation estimates between milk yield and % of fat and % of protein were low. These results showed that the genes affecting milk yield have an antagonistic effect on % of fat and % of protein traits. Its suggests that selection to increase milk yield, would in the long term probably cause a reduction in milk constituents